«... ὡς ὁ κώδικάς της τὀ δείχ νει...» : ῾ Η χρήση τῶν «κωδίκων» ναῶν καὶ μονῶν ὡς τεκμ ηρίων - ΚΑΡΥΔΗΣ, Σπυρος (Byzantina Symmeikta, 2025)
The subject of this study concerns wall inscriptions found in churches and monasteries, which are often referred to as "codes" in the Ionian Islands and mainland Greece. The research is based on both published and unpublished archival sources that document the transcription of these inscriptions and their use in legal disputes among founders in the region of Corfu. The archival material spans from the 16th to the 18th century and originates from the rich notarial archives of Corfu. Specifically, the study examines: the semantic nuances of the term; the reasons why church founders, as well as local ecclesiastical and civil authorities, undertook their official transcription and documentation; the procedures followed during transcription; their use as evidence of ownership and founder rights; their relationship to notarial documents drawn up for churches and monasteries by the founders; and their preferential use as legal evidence in disputes among founders, in contrast to other written records.